Responses of estuarine circulation to the morphological evolution in a convergent, microtidal estuary - Rui Zhang; Bo Hong; Lei Zhu; Wenping Gong; Heng Zhang (Ocean Science, 2022)
The Huangmaohai estuary (HE) is a funnel-shaped microtidal estuary in the west of the Pearl River Delta (PRD) in southern China. Since China reformed and opened up in 1978, extensive human activities have occurred and greatly changed the estuary's topography and modified its hydrodynamics. In this study, we examined the morphological evolution by analyzing remote sensing data with ArcGIS tools and studied the responses of hydrodynamics to the changes in topography from 1977 to 2010 by using the Delft3D model. We took the changes in estuarine circulation during neap tides in dry seasons as an example. The results show that human reclamation caused a narrowing of the estuary, and channel dredging deepened the estuary. These human activities changed both the longitudinal and lateral estuarine circulations. The longitudinal circulation was observed to increase with the deepening and narrowing of the estuary. The lateral circulation experienced changes in both the magnitude and pattern. The momentum balance analysis shows that when the depth and width changed simultaneously, the longitudinal estuarine circulation was modulated by both the channel deepening and width reduction, in which the friction, pressure gradient force, and advection terms were altered. The analysis of the longitudinal vortex dynamics indicates that the changes in the vertical shear of the longitudinal flow, lateral salinity gradient, and vertical mixing were responsible for the change in the lateral circulation. The changes in water depth are the dominant factors affecting lateral circulation intensity. This study has implications for sediment transport and morphological evolution in estuaries heavily impacted by human interventions.